2012
DOI: 10.1016/j.ejmech.2012.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Novel peptidomimetic compounds containing redox active chalcogens and quinones as potential anticancer agents

Abstract: CitationNovel peptidomimetic compounds containing redox active chalcogens and quinones as potential anticancer agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 47 publications
0
31
0
1
Order By: Relevance
“…Furthermore, we have also shown that the tellurium containing compounds 6 and 5 are generally able to enhance the oxidation of thiols in the presence of H 2 O 2 , using a simple in vitro thiophenol oxidation assay. 11,12 In continuation of our previous work, the ROS levels in (the more robust) A 431 cells were monitored using the standard fluorescent 2`, 7` dichlorodihydrofluorescin diacetate (DCHFA) assay, which can be considered as a general ROS indicator, as DCHFA reacts readily with most common ROS, including H 2 O 2 , lipid hydroperoxides and ONOO − . 17 As suspected, in the concentration range used, sulfur and selenium based compounds were unable to disturb the ROS levels in A 431 melanoma cells over a 1 h treatment period.…”
Section: 3 M E C H a N I S Ti C S Tu D I E Smentioning
confidence: 99%
“…Furthermore, we have also shown that the tellurium containing compounds 6 and 5 are generally able to enhance the oxidation of thiols in the presence of H 2 O 2 , using a simple in vitro thiophenol oxidation assay. 11,12 In continuation of our previous work, the ROS levels in (the more robust) A 431 cells were monitored using the standard fluorescent 2`, 7` dichlorodihydrofluorescin diacetate (DCHFA) assay, which can be considered as a general ROS indicator, as DCHFA reacts readily with most common ROS, including H 2 O 2 , lipid hydroperoxides and ONOO − . 17 As suspected, in the concentration range used, sulfur and selenium based compounds were unable to disturb the ROS levels in A 431 melanoma cells over a 1 h treatment period.…”
Section: 3 M E C H a N I S Ti C S Tu D I E Smentioning
confidence: 99%
“…GPx targets redox sensitive thiol proteins, while simultaneously generating reactive oxygen species at a critical threshold. Thus, these drugs act as ROS-users and ROS-enhancers to affect downsteam targets [37]. This action would complement the mechanism of action of β-lap, since death caused by this agent relies upon the hyperactivation of PARP1, which is stimulated by ROS (H 2 O 2 ) [24].…”
Section: Introductionmentioning
confidence: 99%
“…The component variations, postmodifications and secondary transformations will also be discussed. For general information about MCRs, IMCRs and their applications in the synthesis of biologically relevant heterocycles, the reader is directed towards more comprehensive reviews and monographs [13,18,19,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the advancement of the reaction was only depicted on the basis of various catalysts explored, neglecting its synthetic applications, scopes and secondary transformations. With this in mind and our interest in MCRs and drug discovery [18][19][20][21][22][23], we herein summarize the efforts of the chemical community in the progress and applications of GBBR since 1998. This review will cover the biological profiles, synthetic scopes and respective proposed mode(s) of action of GBBR products.…”
Section: Introductionmentioning
confidence: 99%